PRESERVING THE CULTURAL HERITAGE TO ELEVATE SARAWAK TOURISM - Qistina Donna, Lee Abdullah; Norsyahbany, Mansor; Aimuni Athirah, Latif (2021)
This paper is to analyse the factors of awarenessofthe Sarawak Malay embroidery to local community. Qualitative method was applied to gain the information of this issue through interview session and site observation. The focusing factor of awareness of Selayah Keringkamare location, community participation and heirloom.The field of observations have been coded and analysed accordingly through Interpretative Analysis of visualdocumentation. These factors are vital to be emphasized in ensuring that this heritage embroidery is preserved and remains as one of the heritage products that elevate cultural and heritage tourism in Sarawak in particular.